Analisis Unsur Intrinsik Gurindam 12 Raja Ali Haji Pasal 7 - Keysa Azahra; Resa Novianti; Hasanah Hasanah; Tiara Eka Rahmawati Puteri (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Raja Ali Haji wrote Gurindam 12 with the aim of providing life guidance to the Malay community in order to lead a good life, have noble character, and obey God. Gurindam 12, including Chapter 7, not only contains universal moral values, but also messages that were relevant to the Malay society at that time and prioritized status and honor in social life. Through the work, Raja Ali Haji tries to convey the importance of learning, science and wisdom in building a better civilization and urges people to always maintain good morals and avoid bad deeds. The purpose of this research is to reveal the intrinsic elements of gurindam so that it can be read, and is useful for the community. Theoretically, the benefit of this research is to provide input for learning Old Malay Literature to provide teaching materials regarding the elements of literary works, especially in the old poetry genre